2001
DOI: 10.1254/jjp.87.164
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of α-Tocopherol in Renal Ischemia-Reperfusion in Rats

Abstract: ABSTRACT-We evaluated the effects of =-tocopherol (vitamin E) on the products of lipid peroxidation and serum creatinine levels in a rat model of renal ischemia-reperfusion. The animals were submitted to sham operation or renal ischemia-reperfusion, and they were pretreated with =-tocopherol or the vehicle saline. In four groups, we analyzed the lipid peroxidation products by measuring malondialdehyde and chemiluminescence levels. In the other three groups, we studied the serum creatinine levels after the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 8 publications
0
28
1
3
Order By: Relevance
“…Experimental models of ischemia and reperfusion are long described and widely found in the literature 16,[19][20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental models of ischemia and reperfusion are long described and widely found in the literature 16,[19][20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Some authors have also studied shorter clamping times with similar reperfusion periods with renal pedicle or single limb artery clamping, suggesting questionable benefit of its use. [17][18][19][20][21] We believe that these conflicting results are related to short clamping periods, some of what could even controversially work as preconditioning protective factor. Another major difference is the potential to create significant IRI, which is long known to be When comparing electrolytes, no statistically significant difference between groups on the levels of Sodium (p>0.05) and Calcium (p>0.05) were found.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] The protective effects of vitamin E on kidney tissue including renal ischemia reperfusion injury have yielded that it reduces lipid peroxidation and positive effects to antioxidant system status. [1,14,15] In light of the above findings, the present study examined the protective effects of exogenous melatonin and vitamin E supplementation on renal function, antioxidant status, lipid peroxidation production, and histopathological and electron microscopic changes in renal ischemia-reperfusion injury.…”
Section: T Aktoz Et Almentioning
confidence: 99%
“…[1] Ischemia of an organ or system results in varying degrees of tissue destruction, depending on the duration and extent of occluded arterial blood flow. Organ transplantation offers the best chance of studying clinical and experimental ischemia-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants have been found to protect renal cells from cellular injury induced by I/R. [22][23][24] The finding of the anti-oxidant effect of hydrogen and its therapeutic value led us to suggest that endogenous hydrogen may play an important physiological role in maintaining homeostasis. Several studies have shown that hydrogen exerts cytoprotective effects after various types of injuries.…”
Section: Discussionmentioning
confidence: 99%